The Arch of Triumph (H.S. Crocker Co., Inc.)
The Arch of Triumph, between the Court of Flowers and the Court of Reflections at the Golden Gate International Exposition, San Francisco, is mirrored in pools and fountains colored with reflections of tropical vines and plants.